PENCARIAN DAN PENGHAPUSAN FILE DUPLIKAT PADA MEDIA PENYIMPANAN KOMPUTER DENGAN ALGORITMA CRC32 - Indra M. Sarkis S (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2017)
The use of computers in general, are sometimes unaware of file storage, file format with the same type and with a different file name, the computer storage media over and over again. This often occurs when downloading files from the Internet or copy files from other storage media whose file names are different but the content of the same file. In this study CRC 32 algorithm is used as a tool or a subset to search for duplicate files by comparing files with each file to another by reading the checksum value of a file and then compare it with another file checksum value. If the checksum value of some of those files are the same, then the files are declared equal or duplicated even if the file name is different. Outcomes of this research is a software to find and remove duplicate files on computer storage.